Portrait of a collector (Humlebaek : Louisiana Museum of Modern Art, 1986)
Alechinsky, Pierre ; Appel, Karel ; Basquiat, Jean Michel ; Dubuffet, Jean ; Fay, Joe ; Gillet, R.E. ; Hafftka, Michael ; De Jaeger, Stefan ; Jorn, Asger ; Reinhoud ; Vandercam, Serge ; Van Velde, Bram
Portrait of a collector / Portraet af en samler : Stephanie Janssen, Louisiana Museum of Modern Art, Humlebaek, April 5th - May 11 th, 1986 ; University Art Museum, California State University, Long Beach, USA, January 27th - March 8th, 1987
boek